Tunable discontinuous shear thickening with magnetorheological suspensions. (January 2018) - Bossis, Georges; Grasselli, Yan; Meunier, Alain; Volkova, Olga
Discontinuous shear thickening is a phenomenon observed in concentrated suspensions where, at a given applied stress, the flow becomes suddenly partially blocked and the shear rate begins to decrease and to oscillate when the stress is increased above the critical one. In this work, we show that it is possible to control with a magnetic field this abrupt transition from a flowing state to a jammed state, using a suspension of magnetic particles coated with a superplastifier molecule. In the case of experiments made at constant velocity, the transition to the jammed state corresponds to a very high jump of stress which can reach several hundred pascals for fields as low as a few kiloampere per meter. We present also results obtained in microgravity on a magnetic powder, showing that the solid friction between particles plays a key role in the jamming phenomenon.